The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1016/j.apsusc.2010.12.056
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive coating on titanium implants modified by Nd:YVO4 laser

Abstract: Apatite coating was applied on titanium surfaces modified by Nd:YVO 4 laser ablations with different energy densities (fluency) at ambient pressure and atmosphere. The apatites were deposited by biomimetic method using a simulated body fluid solution that simulates the salt concentration of bodily fluids. The titanium surfaces submitted to the fast melting and solidification processes (ablation) were immersed in the simulated body fluid solution for four days. The samples were divided into two groups, one unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 30 publications
2
13
0
1
Order By: Relevance
“…Surface modification by laser beam was shown to be a promising method for treatment of implant surfaces because it is clean, reproducible and economically viable (Cho & Jung, 2003;Sisti, et al, 2013). It is considered clean because it does not interact with external materials during the surface characterization process has a high degree of purity and roughness capable of promoting good osseointegration, and, furthermore there is no contamination of the oxide layer of titanium, since the technique does not use chemical elements (Filho, et al, 2011). The laser applied is of high intensity carried by optical fibers, which results in a greater homogeneity of this intensity on the surface of the implant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Surface modification by laser beam was shown to be a promising method for treatment of implant surfaces because it is clean, reproducible and economically viable (Cho & Jung, 2003;Sisti, et al, 2013). It is considered clean because it does not interact with external materials during the surface characterization process has a high degree of purity and roughness capable of promoting good osseointegration, and, furthermore there is no contamination of the oxide layer of titanium, since the technique does not use chemical elements (Filho, et al, 2011). The laser applied is of high intensity carried by optical fibers, which results in a greater homogeneity of this intensity on the surface of the implant.…”
Section: Discussionmentioning
confidence: 99%
“…The laser presents the physicochemical properties of the formation of an oxygen-rich layer and the incorporation of nitrogen during the rapid melting and solidification of titanium (Gaggl, et al, 2000;Braga, et al, 2007;Queiroz, et al, 2013;Sisti, et al, 2013). The modification of the surface by laser beam leads to the formation of erosions on this surface, making it rough (Filho, et al, 2011). Cho and Jung (2003) compared machined implants with a laser-modified surface by means of topographic analysis (SEM) and reported that the laser-modified surface had regular cavities similar to those of a honeycomb, while the machined surface was relatively smooth and with typical machining signals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 38 ] The fi eld intensity which is localized in the Titanium and its alloys are widely used clinically as orthopedic and dental implants, artifi cial hip joint and coronary stent, because of their excellent chemical and physical characteristics, such as high corrosion resistance, light weight, high mechanical strength, high melting point, and good biocompatibility. [1][2][3][4][5][6][7][8] For advanced applications of titanium implants, most of the frontier researches are being conducted along the following two type of directions: i) Improving osseointegration, i.e., boosting proliferation rate and adhesion of cells onto bone-implant interface, by surface texturing, [8][9][10][11][12] hydroxyapatite (HA) coating, [13][14][15] and bone morphogenetic protein-2 (BMP-2) immobilizing. [ 16 ] Among these technologies, including surface texturing by chemical etching, [ 17 ] lithography, [ 18 ] and sand blasting, [ 19 ] an open problem lies in the diffi culty in producing micro-nano hierarchical structures on titanium implant surfaces, where both the micro-and nanolevel architectures play their indispensable role for enhancing cell adhesion.…”
Section: Doi: 101002/admi201500058mentioning
confidence: 99%
“…Observou-se que as amostras tratadas com laser na fluência de 280 J cm As amostras tratadas termicamente tiveram um aumento na produção de partículas esféricas, que são típicas da fase de hidroxiapatita, produzidas pela difusão térmica, que pode ser explicado pelo aumento na cristalinidade do recobrimento (FILHO, et al, 2011).…”
Section: Texturização De Laser De Excimerunclassified